2017
DOI: 10.22271/tpr.2017.v4.i1.007
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy testing and germination frequency determination of Psoralea corylifolia L., an endangered medicinal plant

Abstract: Seed dormancy is one of important factor which prevent the cultivation of medicinally important plant Psoralea corylifolia. Mechanical dormancy is present in the seed due to hard seed coat. P. corylifolia is a slow growing species due to low germination percentage (5-7%). Long gestation period and delicate field handling discourages the commercial cultivation of the plant so different treatments were used to break dormancy in seeds. Out of five different methods used 98% concentrated H 2 SO 4 for about one hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Seeds were considered germination with the emergence of radical. The germination percentage was determined by counting the number of seeds germinated during the experiment period (six days) over the total number of seeds according to Equation (1), [1].Germination%=NumberofgerminatedseedsTotalnumberofseeds×100…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Seeds were considered germination with the emergence of radical. The germination percentage was determined by counting the number of seeds germinated during the experiment period (six days) over the total number of seeds according to Equation (1), [1].Germination%=NumberofgerminatedseedsTotalnumberofseeds×100…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…[3]. However, several reports have indicated that PC is regarded as an endangered medicinal plant in India, so the research of this plant has attracted much attentions [4,5]. Modern pharmacological studies have shown that the dried fruit of the plant has anti-bacterial [6], anti-diabetic [7], anti-depressant [8], anti-oxidative [9], anti-fungal [10], anti-inflammatory [11], and many other effective activities.…”
Section: Introductionmentioning
confidence: 99%